IMF Staff papers, Volume 46 No. 3. (IMF Staff Papers; IMF Staff Papers, 1999)
This paper examines determinants and leading indicators of banking crises. The paper examines episodes of banking system distress and crisis in a large sample of countries to identify which macroeconomic and financial variables can be useful leading indicators. The best warning signs of the recent Asian crises were proxies for the vulnerability of the banking and corporate sector. Full-blown banking crises are shown to be associated more with external developments, and domestic variables are the main leading indicators of severe but contained banking distress.